Eksplorasi Keefektifan Pembelajaran Daring pada Masa Pandemi Covid-19 di FKIK Universitas Warmadewa - I MADE PARIARTHA (Universitas Hang Tuah, 2023)
Covid-19 pandemic has brought about a fundamental change in the field of Medical Education. Medical education due to the Covid-19 pandemic must be carried out online. FKIK Unwar applies online learning at the academic level. The aim of the study was to obtain data on the effectiveness of online group discussions, tutor behavior in facilitating online group discussions, student motivation, students' perception of the learning environment and knowing the factors that support and hinder the implementation of online learning at FKIK Unwar. This study is a mixed method. Quantitative research by distributing DREEM, TGEI, IMI, and TBQ questionnaires to students. Qualitative research to find out the factors that support and inhibit online learning is carried out with FGD to students and lecturers. Most respondents > 75% agreed and strongly agreed on each of the DREEM, IMI, TGEI, TBQ questionnaires. FGD results there are several factors that support online learning, among others: Facilitation of online skills learning through LMS and the ability of lecturers in facilitating online learning. Some of the factors that hinder include: The internet network is sometimes unstable, not optimal institutional assistance in supporting the implementation of online learning, and supporting online learning, especially in terms of clinical skills has not been optimal. Online learning at FKIK Unwar is already underway effectively. Intrinsic motivation of students in following online learning is quite good. Tutors are able to facilitate online learning well. Students perceive the online learning environment at FKIK Unwar going well.